2018
DOI: 10.3390/nu10101354
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Intake and Sleep Disorder Symptoms: Findings from the Jiangsu Nutrition Study of Chinese Adults at Five-Year Follow-Up

Abstract: (1) Background: In clinical trials, dietary magnesium use can improve insomnia symptoms. However, little is known about the association between dietary magnesium consumption and sleep disorder symptoms including daytime falling asleep, sleepiness and snoring at the population level. (2) Methods: We used data from 1487 adults aged 20 and above attending the Jiangsu Nutrition Study. At baseline in 2002, dietary magnesium was assessed by 3-day weighed food records. At follow-up in 2007, sleep disorder symptoms, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 30 publications
2
27
1
2
Order By: Relevance
“…An analysis of the 2007–2008 NHANES found that lower magnesium intake was associated with very short (<5 h) sleep [15]. A cohort study of 1056 participants recruited into the Jiangsu Nutrition Study (JIN) from 2002 to 2007 found that dietary magnesium consumption was inversely associated with falling asleep during the day in women but not in men [35], which parallels our findings in night time sleep duration. Abbasi et al demonstrated in a double-blind placebo-controlled trial with elderly subjects who received 500 mg magnesium or placebo daily for 8 weeks that magnesium supplementation increased sleep time, sleep efficiency, and serum melatonin concentration, and decreased Insomnia Severity Index score, sleep onset latency, and serum cortisol concentration compared to placebo [36].…”
Section: Discussionsupporting
confidence: 73%
“…An analysis of the 2007–2008 NHANES found that lower magnesium intake was associated with very short (<5 h) sleep [15]. A cohort study of 1056 participants recruited into the Jiangsu Nutrition Study (JIN) from 2002 to 2007 found that dietary magnesium consumption was inversely associated with falling asleep during the day in women but not in men [35], which parallels our findings in night time sleep duration. Abbasi et al demonstrated in a double-blind placebo-controlled trial with elderly subjects who received 500 mg magnesium or placebo daily for 8 weeks that magnesium supplementation increased sleep time, sleep efficiency, and serum melatonin concentration, and decreased Insomnia Severity Index score, sleep onset latency, and serum cortisol concentration compared to placebo [36].…”
Section: Discussionsupporting
confidence: 73%
“…On the other hand, the sleep duration values decreased significantly in the CG, whereas but no change was observed in the EG. These findings are in accordance with previous reports, which observed no improvements in sleep quality after TRY [52,53] ingestion and no associations between dietary MG consumption and sleepiness [54] Thus, these controversial finding, that the participants did not improve their sleep quality, could be related to the dosage of TRY and MG micronutrients. Therefore, the RDA established by the National Academy of Sciences [30] and the higher doses of TRY and MG (60 mg of TRY and 60 mg of MG per day) previously recommended [31] were not enough to improve sleep quality in women with fibromyalgia.…”
Section: Discussionsupporting
confidence: 92%
“…Magnesium supplementation improves sleep efficiency, sleep time and sleep onset latency, early morning awakening, and insomnia objective measures such as the concentration of serum renin, melatonin, and serum cortisol, in older adults [8]. Dietary magnesium intake may have long-term benefits in reducing the likelihood of daytime falling asleep in women [9]. Anxiety can cause insomnia, and vice versa which can result in a self-perpetuating cycle, which leads to chronic insomnia.…”
Section: Introductionmentioning
confidence: 99%